Analysis of Content Creator-Based Learning Among PGSD’ Students on Public Speaking Ability - Syaiful Hidayat; Karmila Risa Rahmawati; Dela Maulana; Indri; Fitriani (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
In today's era of rapid technological advancement and widespread information flow, there remains a gap in individuals' ability to communicate effectively through digital platforms, particularly among university students both in text and video formats. This indicates that technological progress does not necessarily equate to improved digital public speaking skills. Therefore, this study aims to analyze the implementation of content creator-based digital learning on the public speaking abilities of elementary teacher education students at Universitas Madako Tolitoli. Using a qualitative method with a phenomenological approach, the research involved ten sixth-semester students. Data were collected through direct observation, in-depth interviews, and documentation of the produced content. The data were then analyzed through reduction, presentation, and conclusion drawing. The findings reveal that content creator-based learning significantly enhanced students’ average confidence (4.57), fluency (5.00), structured delivery (4.76), and creativity (4.72). This study contributes to the development of digital learning models by demonstrating that the integration of content creator-based approaches effectively improves students' public speaking skills while also identifying technical constraints that must be addressed to optimize the use of technology in higher education.